The impacts of CEO ownership and origin on firm performance: evidence from an emerging economy - Siregar, M. Edo Suryawan; Oktapiani, Oktapiani; Ahmad, Gatot Nazir (Global Advances in Business Studies, 2023)
This study aims to determine the effects of CEO ownership and CEO origin on the performance of non-financial firms listed on the Indonesia Stock Exchange from 2010–2018. The data used in this study were taken from annual reports of firms in non-financial sectors published by the Indonesia Stock Exchange from 2010–2018. This study utilized a purposive sampling technique to obtain 1,976 observations. The research model used is an unbalanced panel data analysis with a fixed-effect model approach. The results show that CEO ownership has a significant effect on firm performance when measured using Tobin’s Q as a market proxy. However, CEO origin does not have a significant effect on Tobin’s Q.